HINDUTVA: CULTURAL AND RELIGIOUS RESPONSE - Chackalackal, Saju (Journal of Dharma, 2004)
Religion is an existential entity emerging from the coming together of people with the intention of realizing their deepest yearning for a communion among themselves culminating in a communion with the Transcendental Reality; it results from their continued attempt to establish a holistic communion among nature, human beings and the Supernatural. This seems to require a perspective different from that which they normally cultivate in dealing with the natural course of events. This has been a constant phenomenon from the inception of humanity, and, in the course time, has become a vital element in the transformation of human psyche as well. The yearning for a lasting communion – natural (human) as well as supernatural – is so deep to human beings so much so that the internal dynamics and the external forms of religion that have evolved over the ages exercise a great emotional appeal among the adherents of any religion. Since religion is so natural to the human society, it must be admitted that this emotional aspect of religion has been a positive and creative force in vitalising and renewing the human spirit in different civilisations and political identities, and instrumental in bringing forth lasting and effective transformation in human society. We shall not ignore, at the same time, the fact that the same force has played havoc in setting persons, families, communities, cultures and civilisations against each other, orientating the human spirit diametrically against its deepest need for communion among human beings. Both these trends can be traced at every stage of the development of cultures and, thus, in the history of humanity.